Assessing Rape Myth Acceptance: A Contribution to Italian Validation of the Measure for Assessing Subtle Rape Myth (SRMA-IT). (June 2022) - Martini, Mara; Tartaglia, Stefano; De Piccoli, Norma
The study aimed to validate the Italian version of the Measure for Assessing Subtle Rape Myths developed by McMahon and Farmer. A sample of 3, 915 university students (70.8% female) completed the questionnaire. After an exploratory factor analysis, a confirmatory factor analysis tested the resulting four-factor structure of the Italian Subtle Rape Myth Acceptance (SRMA-IT) Scale ("She Asked for It"; "He Didn't Mean To"; "It Wasn't Really Rape"; and "She Lied"), consistent with McMahon and Farmer's initial hypothesis. The Italian validation did not include items related to intoxication. Internal consistency of the subscales was good (α from .78 to .90). Convergent validity between all subscales and System Justification–Gender was detected: A strong relationship was observed ( r is from .19 to .33; p < .001). The independent-sample T test then showed that women accepted all four rape myths significantly less than men: Effect size is more than moderate for the myth "She Asked for It" (Cohen's d = .60) and between small and moderate for the other myths ( d is from .35 to .42). Acceptance of rape myths is often associated with higher men's proclivity to rape and with tendency to raped women's double victimization (they can be not believed or blamed when they disclose the rape). Having a validated instrument to measure rape myth acceptance can enhance empirical research on this topic and help to develop interventions of prevention both for men in the society and for the first responders to disclosures, also sustaining a culture of respect and of contrast to violence.